Faktor-faktor yang Mempengaruhi Rumahtangga Rawan Pangan di Kota Pekanbaru - Purwati, Purwati; Afriyanni; Agusyani; Agustina Pujiwati, Lina; Rifai, Ahmad; Gevisioner; Sonia Ningsih, Siska (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
Abstract: Household food security is an important part of shaping regional food security. This study aims to determine the factors that influence food insecurity at the household level in Pekanbaru City using Susenas data from March 2022. Descriptive statistical analysis to describe household characteristics and multinomial logistic regression analysis to analyze the influence of household characteristics variables on household food insecurity status in Pekanbaru City. The level of household food security using the Food Insecurity Experience Scale (FIES), a global indicator that has not been widely explored in previous studies. The results of this study indicate that savings ownership, food expenditure share, protein consumption level, education level, poverty, access to credit, gender and age group and BPNT have an effect on the level of household food insecurity in Pekanbaru City. This study recommends that local governments can optimize intervention policies for food insecure households by focusing on certain characteristics, such as female household heads, ever-married status, not receiving BPNT, no savings, poor, and lacking Protein Consumption Level (TKP) and Energy Consumption Level (TKE), through a comprehensive approach that includes increasing knowledge, education, improving economic capabilities, and expanding social assistance services. Keywords: household food security, Food Insecurity Experience Scale, multinomial logistics